Perubahan Bervariasi dalam Ekranisasi Manga Death Note Karya Tsugumi Ohba dan Takeshi Obata ke dalam Drama Death Note Karya Inomata Ryuichi - Setyawati, Ni Wayan Nadia; Damayanti, Silvia; Ari Sulatri, Ni Luh Putu (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2021)
This research is entitled "Variety Changes in the Ecranization of the Death Note Manga by Tsugumi Ohba and Takeshi Obata into the Death Note Drama by Inomata Ryuichi". The purpose of this study is to provide an understanding of ecranization with sources in the form of manga related to changes in intrinsic elements. The research method used is descriptive qualitative method. The data sources used in this study are the Manga Death Note by Tsugumi Ohba & Takeshi Obata and Drama Death Note by Inomata Ryuichi. The theory used in this research is Ecranization Theory proposed by Eneste and Structural Theory by Nurgiyantoro. The results of this study indicate that there is a change in the intrinsic elements contained in the manga into drama. These changes are in the form of varied changes that occur in the plot, characters, and setting of the place. These varied changes aim to change the story, atmosphere, impression, role, and adjust production costs.